Holmium laser enucleation of the prostate: patient selection and perspectives - Marien T (Research and Reports in Urology, 2016)
Tracy Marien, Mustafa Kadihasanoglu, Nicole L Miller Department of Urology, Vanderbilt Medical Center, Nashville, TN, USA Background: Multiple endoscopic surgical options exist to treat benign prostatic hyperplasia (BPH), including holmium laser enucleation of the prostate (HoLEP). HoLEP alleviates obstructive prostatic tissue via enucleation, both bluntly with a resectoscope and by cutting tissue with the holmium laser, and removal of adenoma via morcellation. This article reviews patient selection for HoLEP in order to optimize outcomes, costs, and patient satisfaction.Methods: A literature review of all studies on HoLEP was conducted. Studies that focused on outcomes in regard to patient and procedural factors were closely reviewed and discussed.Results: Various studies found that men with large or small prostates, on antithrombotic therapy, in urinary retention, with bladder hypocontractility, with prostate cancer, undergoing retreatment for BPH, or in need of concomitant surgery for bladder stones and other pathologies do well with HoLEP, as demonstrated by excellent functional and symptomatic outcomes as well as low complication rates. There is a 74–78% rate of retrograde ejaculation following HoLEP. Techniques to preserve ejaculatory function following enucleative techniques have not been able to demonstrate a significant improvement.Conclusion: Patient selection for HoLEP can include most men with bothersome BPH who have evidence of bladder outlet obstruction and are healthy enough to undergo surgery. The ability to safely perform concomitant surgery with HoLEP benefits the patient by sparing them an additional anesthetic and also decreases costs. Patients should be made aware of the risk of retrograde ejaculation following HoLEP and counseled on treatment alternatives if maintaining ejaculatory function is desired. Keywords: holmium laser nucleation of the prostate, HoLEP, benign prostatic hyperplasia, prostate size, urinary retention, patient selection